Acerca de los estilos cognitivos: dependencia- independencia de campo - Meza, Anibal (Pontificia Universidad Católica del Perú, 1987)
A brief review of literature on Field Dependence - Independence (FD - FI) Cognitive Styles is presented here. Absence of research made in Peru on the subject is noted and the area covered by FD- FI subject is delimited. Origins of FD - FI as constructs are taken into account, anchoring them to major construct "psychological differentiation". Modes of testing are reported and traits of FD - FI as cognitive styles are enlisted (they are pervading dimensions of individual functioning, proccss variables, bipolar and neutral in value). Relationships FD-FI - interpersonal behavior are considered: type of interpersonal orientation, responsivity to social clues and intercsts and typical interpersonal responses. Finally, ontogenetic (review restricted to effects of training and child rearing) and cultural origins of FD - Fl are examined.